Староверы в контексте русской культуры XIX–XX вв. (по материалам полевых экспедиций последних лет) - Александровна Агеева, Елена (Slavistica Vilnensis, 2001)
The article focuses on the unique history of small and rare Old Believer communities, which avoided any state regulation of their faith. Their original culture are written heritage have now become available for research, thanks to Moscow University archeographic expeditions from the 1980’s and 1990’s. Study of traditional Russian culture in the Volga region and the North Caucusus has made it possible to isolate and describe a number of communities, each with its own understanding of their “tzar’s way” (“carskiy putj”, that is, their history of going away from secular world), but they never compromised on significant theological issues, preferring wandering, withdrawal, and polemics. The world outlook of subsequent adherents of non-state confessions is reflected in their writings, correspondence, and ecclesiastical verse. The development of Old Russian literary traditions is traced in the works both of anonymous authors, and of newly discovered ones: the monk Grigori Rezaev, and Kilin (b. 1916), whose works together form an encyclopaedia of Old Believer life. To this day, not all communities have been able to devise mechanisms for preserving and passing down their tradition, but their centuries of experience in development outside the scope of state regulation is extremely important to our understanding of the future of traditional culture.